THE LEGAL STATUS OF CHILDREN OUTSIDE MARRIAGE: A COMPARATIVE STUDY OF CIVIL LAW IN INDONESIA AND MALAYSIA - Mahendra, Yusril; Izzuddin, Ahmad; Alfikri, Ahmad Faiz Shobir; Rahmatullah, M. Azam (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The legal status of children's validity raises conflicts between das sein and das sollen, especially about religious values, children's interests, and legal developments in Indonesia and Malaysia. This research aims to analyze and compare the Decision of the Constitutional Court of the Republic of Indonesia No. 46/PUU-VIII/2010 and the Decision of the Rayuan Sivil Court of Malaysia No. W-01 (A) - 365-09/2016 regarding the legal status of children out of wedlock so that similarities and differences can be identified in terms of legal substance, legal considerations, and legal implications for the protection of the rights of children out of wedlock in Indonesia and Malaysia. The method used in this research is normative legal research with a comparative legal approach. The result of this research is that the validity of the status of children out of wedlock is legally recognized in Indonesia and Malaysia. The Decision of the Constitutional Court of the Republic of Indonesia No.46/PUU-VIII/2010 explains that children out of wedlock have a civil relationship not only with their mother and mother's family but also with the man who is the father, provided that the relationship can be proven through science and technology or other evidence that is valid according to law. In Malaysia, based on the Rayuan Sivil Court Decision No W-01 (A) - 365-09/2016, children of Muslim couples born out of wedlock can now be attributed to their biological father. Although the two decisions have the same legal substance, the reasons underlying the birth of the two decisions are different. The Constitutional Court of the Republic of Indonesia made social justice, legal certainty, and protection of children's rights as citizens guaranteed by the constitution (UUD 1945) legal considerations. However, the Court of Civil Procedure is oriented towards administrative regulations based on the 1957 BDRA Deed Seksyen 13